Guide for making acute risk decisions (John Wiley & Sons, Inc. ; American Institute of Chemical Engineers, 2020)
"This book presents a guidance on a large range of decision aids for risk analysts and decision makers in industry so that vital decisions can be made in a more consistent, logical, and rigorous manner. It provides good industry practices on how risk decision making is conducted in the chemical industry from many risk information sources as well as all the elements that need to be addressed to ensure good decisions are being made. Topics include : identifying risk decisions, a risk decision strategy for process safety, case studies in risk decision making failures, guidance on selecting decision aids, templates for decision making in risk-based process safety, understanding process hazards & worst possible consequences, management of change as an exercise in risk identification, inherently safer design as an exercise in risk tradeoff analysis, using LOPA and risk matrices in risk decisions, using CPQRA and safety risk criteria in risk decisions, group decision making, avoiding decision traps, documentation of process safety risk decisions"--